PENGARUH MODEL PEMBELAJARAN DAN GAYA BELAJAR TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS X SMK NEGERI 2 WATAMPONE - Rusnilawarni Rusnilawarni (Chemistry Education Review (CER), 2017)
This research aims to identify the influence of interaction instructional model and learning style to critical thinking ability of students in class X SMK Negeri 2 Watampone in electrolyte and nonelectrolyte solution. The type of research is quasi-experimental using factorial design 2x3. Population of the research is all of studentsin class X SMK Negeri 2 Watampone school year 2014/2015 consist of 9 class, which amounted to 288 students. The sample is taken by twice of purposive sampling, and the selected classesis X TITL 1 (electric installation technique) and X TITL 2. The Hypothesis test is conducted by SPSS 20 Program using two way Anova. The results of descriptive statistic are average critical thinking ability that students taught using inquiry learning model and cooperative tipe articulation learning are 75.78 and 66.40. Average score critical thinking ability of learners who have learning styles kinethetic, visual and auditory are 73.34, 65.00 and 63.15. The results of this study show that (1) There is no  influence of instructional model to critical thinking abilityof students in class X SMK Negeri 2 Watampone in electrolyte and non electrolyte solution, (2) There is no influence of visual learning style, auditory and kinesthetic toward the critical thinking abilityof students in class X SMK Negeri 2 Watampone in electrolyte and non electrolyte solution, (3) There is an interaction between the instructional model and learningstyles in influencing the critical thinking ability of students in class X SMK Negeri 2 Watampone in electrolyte and non electrolyte solution. Tukey HSD test result show that critical thinking ability of learners who have learning styles kinesthetic higher than the learners who have visual and auditory learning styles, and than critical thinking ability of learners who have learning styles visual and auditory learning style is not different.